On the meaning of the logogram LÚ(.MEŠ)MAŠ.EN.KAK in Hittite cuneiform - B. E. Alexandrov (Шаги, 2024)
The article is devoted to the use of the logogram LÚ(.MEŠ)MAŠ.EN.KAK in Hittite texts. This logogram was borrowed from Mesopotamian cuneiform, in which it rendered the Akkadian word muškēnum (lit. ‘the one who bows down, performs proskynesis’). In 1950 E. Laroche showed that the logogram should be read as ašiwant- ‘poor’ in Hittite. However, subsequently several scholars have pointed out that this meaning did not fit well into many contexts. Therefore it was suggested that LÚ(.MEŠ)MAŠ.EN.KAK was rather a social term referring to a certain group of Hittite population dependent of the state (‘palace’) (V. Souček, I. M. Diakonoff). Such renderings of the logogram as ‘semi-free, dependent, serfs, servants’ which are widely used in the literature conform with this interpretation. But there seem to be insufficient evidence in the sources to substantiate these translations. The article analyses two texts from ancient Tapikka (HKM 8, 105) which were not yet known in the 1960s when the main study on the Hittite LÚ(.MEŠ)MAŠ.EN.KAK appeared. It is suggested that the solution should be sought in the Mesopotamian tradition of the Old Babylonian time in which the Akkadian equivalent of the logogram, the noun muškēnum, denoted commoners, ordinary citizens economically independent of the palace.